2016
DOI: 10.3389/fchem.2016.00001
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Crosstalk by Protein Kinases on CFTR Trafficking and Activity

Abstract: Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) is a member of the ATP binding cassette (ABC) transporter superfamily that functions as a cAMP-activated chloride ion channel in fluid-transporting epithelia. There is abundant evidence that CFTR activity (i.e., channel opening and closing) is regulated by protein kinases and phosphatases via phosphorylation and dephosphorylation. Here, we review recent evidence for the role of protein kinases in regulation of CFTR delivery to and retention in the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 104 publications
(150 reference statements)
0
69
0
Order By: Relevance
“…36 PKA phosphorylation sites are highly conserved among species, and the R region has been shown to contain the majority of those sites. 36,37 This region may be likened to a net or web structure that is highly plastic with subregions of disorder and coil where transitions occur between these states when targeted by PKA and other protein kinases. One idea is that a randomly fluctuating R region becomes locally ordered with coil structures after regulation to permit the binding of other proteins to assemble a hub (or hubs).…”
Section: Cftr Protein Structure Remains To Be Fully Elucidatedmentioning
confidence: 99%
“…36 PKA phosphorylation sites are highly conserved among species, and the R region has been shown to contain the majority of those sites. 36,37 This region may be likened to a net or web structure that is highly plastic with subregions of disorder and coil where transitions occur between these states when targeted by PKA and other protein kinases. One idea is that a randomly fluctuating R region becomes locally ordered with coil structures after regulation to permit the binding of other proteins to assemble a hub (or hubs).…”
Section: Cftr Protein Structure Remains To Be Fully Elucidatedmentioning
confidence: 99%
“…This role of SYK in regulating protein trafficking has been reported previously for other substrates, e.g., trafficking a resident of the trans-Golgi network (TGN) 38 [68], the engaged highaffinity IgE receptor (FcεRI) [69], and the small GTPase Rac1 [70] (shown to play a role in CFTR trafficking and membrane anchoring [71]). Recent findings have shown that phosphorylation of CFTR by SYK results in reducing the abundance of CFTR in the plasma membrane [72]. Importantly, SYK-associated CFTR phosphorylation might not be a major determinant in CF patients.…”
Section: Syk and Cystic Fibrosismentioning
confidence: 99%
“…1 The latter is regulated by the protein trafficking machinery, which controls the process through which a membrane protein is delivered from its place of synthesis -the membrane of the endoplasmic reticulum -to its final destination -the plasma membrane (PM). Besides these anterograde trafficking pathways, channels and transporters also undergo endocytosis followed by either recycling to the PM or targeting to the lysosomal compartment.…”
Section: Trafficking and Rab Proteinsmentioning
confidence: 99%
“…These late trafficking events are controlled by several protein partners, that include protein kinases, myosins and small GTPases, among which Rab proteins. 1 Rab GTPases form the biggest subfamily of the Ras superfamily of small GTPases. As most members of this superfamily, they function as molecular switches alternating between 2 conformational status -a GTP-bound active form and a GDP-bound inactive form.…”
Section: Trafficking and Rab Proteinsmentioning
confidence: 99%
See 1 more Smart Citation